U.S. Navy Trieste atmosphere analyzer equipment - General Dynamics Corporation; Interstate Photographers; Larson, Christian du Bois
The photographs depict unidentified men with the Trieste and various pieces of equipment, including a Beckman Mark IV Atmosphere Analyzer. 2012-002_2212 was photographed by Interstate Photographers; 2012-002_2213 and 2012-002_2214 are the work of Christian du Bois Larson; 2012-002_2216 was taken by General Dynamics; 2012-002_2215 is unattributed.
Keywords: Scientific apparatus and instruments; Bathyscaphe; United States. Navy; Trieste (Bathyscaphe); Beckman Instruments, Inc.